FEEDING EFFECT OF INULIN DERIVED FROM Dahlia variabilis TUBER ON INTESTINAL MICROBES IN STARTER PERIOD OF CROSSBRED NATIVE CHICKENS - Krismiyanto, L.; Suthama, N.; Wahyuni, H. I. (Diponegoro University, 2014)
The purpose of the research was to study the effects of feeding inulin derived from Dahliavariabilis tuber powder and extract on the existence of intestinal microbes in crossbred native chickenstarter. Experimental animals were 280 unsex crossbred native chickens and powder and extract ofdahlia tuber as source of inulin, which were started to be fed on day 22. The present experiment wasassigned in a completely randomized design with 7 treatments and 4 replications (10 birds each). Thetreatments were: T0 (basal diet/BD), T1 (BD+0.4% powder form), T2 (BD+0.8% powder form), T3(BD+1.2% powder form), T4 (BD+0.39% extract form), T5 (BD+0.78% extract form), and T6(BD+1.17% extract form). Parameters measured were the number of Lactic acid bacteria (LAB),Escherichia coli, intestinal potential hydrogen (pH) (duodenal, jejunal and ileal), rate of passage anddaily body weight gain (DBWG). Data were subjected to ANOVA and followed by Duncan andpolynomial orthogonal test. The results indicated that feeding inulin derived from dahlia tuber powderand extract form significantly (P<0.05) increased LAB population and DBWG, but decreasedEscherichia coli number and intestinal pH, and slow the rate of passage. In conclusion, feeding inulin ofdahlia tuber powder was optimum at 0.9% but that of extract is linier until 1.17%.